Effect of the tire – Pavement contact at the surface layer when the tire is tilted in bend. (25th October 2021) - Oubahdou, Y.; Wallace, E-R.; Reynaud, P.; Picoux, B.; Dopeux, J.; Petit, C.; Nélias, D.
Highlights: Use of fast Semi analytical method to model tire – pavement contact (compared to FEM) Use of precise tire geometry (estimated by a photogrammetry method) and an equivalent Young's modulus (function of the inflation pressure resulting from a press load tests) Effect of tire inclination in bend (or roundabout) on the calculated shear stresses (origins of damage in turns) Importance of the contact parameters in the degradation of the pavement surface layers. Abstract: Tire-pavement interaction is a rolling contact problem that depends on tire and pavement factors, such as vehicle speed and weight, material and type of tire, tire pressure inflation, camber and texture of the surface layer. In this paper, the problem of tire-pavement contact is studied using a realistic description in normal section and bend. The study focuses on the shape of the contact patch and the stress distribution at the tire-pavement interface and the surface shear stresses rather than internal stresses in the structure of the pavement. The numerical approach introduced requires precise tire geometry (estimated by a photogrammetry method) and an equivalent Young's modulus (function of the inflation pressure resulting from the press load tests). Vertical contact stress at the tire-pavement interface predicted by a Semi-Analytical model were compared to experimental measurements with a press system under different loads and angles of inclination. Finally, we discuss the effect of the tire inclination on the calculated shear stresses (origins of damage in turns). The model shows that the increase of the angle of inclination in a turn has a direct influence on the distribution of the tire-pavement contact stresses and the shear stresses. These results will provide indications for the evaluation of the performance of the surface layer with respect to rutting and downward cracking.